2012
DOI: 10.2172/1182733
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Enhanced Photoemission

Abstract: Next generation ultrabright light sources will operate at megahertz repetition rates with temporal resolution in the attosecond regime. For an X-Ray Free Electron Laser (FEL) to operate at such repetition rate requires a high quantum e ciency (QE) cathode to produce electron bunches of 300 pC per 1.5 µJ incident laser pulse. Semiconductor photocathodes have su cient QE in the ultraviolet (UV) and the visible spectrum, however, they produce picosecond electron pulses due to the electron-phonon scattering. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…with x µ (τ ) on a geodesic parametrized by an invariant parameter τ . The propagator in flat space (37) has indeed the form…”
Section: Appendix E: Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…with x µ (τ ) on a geodesic parametrized by an invariant parameter τ . The propagator in flat space (37) has indeed the form…”
Section: Appendix E: Symmetriesmentioning
confidence: 99%
“…(investigations of the effects of interactions in a non-flat geometry can be found in refs. [27,[30][31][32][33][34][35][36][37][38][39][40][41].) In our simple approximation interactions appear in the form of the inflaton potential.…”
Section: Introductionmentioning
confidence: 99%
“…refs. [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The issue is similar to the understanding of thermalization of arbitrary initial correlation functions in flat space, for which powerful functional methods have been developed [55][56][57][58][59][60][61][62][63][64][65].…”
Section: General Solution For Graviton Correlationmentioning
confidence: 99%
“…The metal photocathode has been researched for a long time and used in many facilities, due to its virtue of high brightness, long lifetime, and low cost. And it has been indicated that it holds great promise to eject a uniform 3D ellipsoid electron bunch with only linear internal space charge fields because of its ultrafast response characteristic, which is an ideal distribution for a high-brightness FEL operation [4][5][6]. But, in order to ensure a high photoemission yield, the metal photocathode usually needs to be pumped by high power ultraviolent laser, which undoubtedly increases the demand and cost for the drive laser [7].In recent years, the plasmon-enhanced photocathode (PEP) attracts more attentions, which introduces the surface plasmon polarizations (SPPs) to enhance the interaction between laser and materials [8].…”
mentioning
confidence: 99%